Tahsin al-Kitabah and al-Khat al-Araby Learning Innovations in the Digital Era - Hasbullah, Abdur Ro'uf; Makhisoh, Iis (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
The emergence of various kinds of technological tools, digital media, and social media are making learning easier, by using online correction systems both in learning Tahsin al-Kitabah and Khat Araby. Apart from that, there are many applications related to khat learning, such as kitabahku, Mashq, Ana Mukhtariful khat, Kelk, and other applications that not only support students in learning Khat but also support the development of their creativity in creating work. This requires educators to utilize digital media as a medium to support learning. The implementation of Tahsin al-Kitabah learning using the